Socioeconomic disparities in cognitive impairment, quality of life, and mortality among older adults in Germany. - Omar Hahad; Jasmin Ghaemi Kerahrodi; Isabel Heinrich; Katharina Geschke; Katja Petrowski; Elmar Brähler; Julia Petersen; Anna C Reinwarth; Julian Chalabi; Alexander K Schuster; Emilio Gianicolo; Karl Lackner; et al. (PLoS ONE)
Background The global older population is increasing, leading to a rise in non-communicable diseases and disabilities, particularly in Western countries. With the aging population expanding and the number of older adults with cognitive impairments expected to rise, there is increasing interest in understanding the socioeconomic disparities associated with cognitive impairment. This study investigates the relationships between socioeconomic status (SES), cognitive impairment, quality of life, and mortality among older adults in Germany. Methods Data from the senior cohort (N = 1,069) of the German Gutenberg Health Study (2017-2024) were analyzed, focusing on older adults aged 75-85 years. Regression modeling with sequential adjustment for covariates was employed to determine the association between various domains of SES (SES index comprising educational background, occupational status, and household net-income) and cognitive impairment (Montreal Cognitive Assessment), quality of life (EUROHIS-QOL), and all-cause mortality. Results Cognitive impairment scores varied significantly by SES with higher SES being associated with better cognitive performance. Among the SES domains, the household net-income score was the strongest predictor of cognitive impairment. Likewise, higher SES was significantly associated with higher quality of life, whereas no association between cognitive impairment and quality of life was found. Additionally, cognitive impairment was significantly associated with higher all-cause mortality, whereas SES did not show a significant association with mortality. No significant interactions between SES and cognitive impairment were observed in relation to quality of life or all-cause mortality. Conclusion Among older adults, SES is strongly associated with cognitive impairment. However, cognitive impairment emerges as a more significant risk factor for all-cause mortality than SES. These findings suggest the need for public health strategies to prioritize cognitive health monitoring and targeted interventions, while simultaneously addressing social inequalities, to reduce the burden of these adverse outcomes.